Films from Glyoxal-Crosslinked Spruce Galactoglucomannans Plasticized with Sorbitol - Kirsi S. Mikkonen; Mari I. Heikkilä; Stefan M. Willför; Maija Tenkanen (International Journal of Polymer Science)
Films were prepared from a renewable and biodegradable forest biorefinery product, spruce O-acetyl-galactoglucomannans (GGMs), crosslinked with glyoxal. For the first time, cohesive and self-standing films were obtained from GGM without the addition of polyol plasticizer. In addition, glyoxal-crosslinked films were prepared using sorbitol at 10, 20, 30, and 40% (wt.-% of GGM). Glyoxal clearly strengthened the GGM matrix, as detected by tensile testing and dynamic mechanical analysis. The elongation at break of films slightly increased, and Young's modulus decreased with increasing sorbitol content. Interestingly, the tensile strength of films was constant with the increased plasticizer content. The effect of sorbitol on water sorption and water vapor permeability (WVP) depended on relative humidity (RH). At low RH, the addition of sorbitol significantly decreased the WVP of films. The glyoxal-crosslinked GGM films containing 20% sorbitol exhibited the lowest oxygen permeability (OP) and WVP of the studied films and showed satisfactory mechanical performance.